The impact of stock delisting from the Shari'ah-compliant list: evidence from Bursa Malaysia - Prima Sakti, Muhammad Rizky; Barom, Mohd Nizam (2014)
In order to be more compatible with the global screening norms, Securities Commission of Malaysia recently introduced a new screening methodology for Shari’ah compliant securities listed on Bursa Malaysia.The new screening criteria was announced on 18 June 2012, and the effective outcome of this is reflected in the list of Shari’ah compliant securities released by the Securities Commission on 29 November 2013. As a result, 158 companies were removed from the list. This paper seeks to analyse the stock price reactions of the affected companies to the announcement of the new screening methodology (Event 1) and their actual delisting from the list of Shari’ah compliant securities (Event 2). The daily abnormal returns of the securities are estimated by employing a market model regression and the calculation of the cumulative abnormal returns (CAR). The estimation period spans from 150 days before the event to 72 days after event date. The findings of this study will provide empirical evidence on the link between Shari’ah compliant status and stock performance of listed companies, particularly on the potential negative impact of being delisted from the list of Shari’ah compliant securities.